Gingival peeling and periodontal aesthetics: a case report. - de Souza Fonseca, Ricardo Roberto; Fernandes de Menezes, Silvio Augusto; Rezende de Albuquerque, Felipe; de Souza Rodrigues, Tânia Maria; Lopes Pereira Neto, Armando Rodrigues (Brazilian Journal of Implantology and Health Sciences, 2020)
Melanic pigmentations (MP) are dark stains located on the masticatory mucosa. These pigmentations are consequence of the excess of melanin production by the melanocytes located in the basal layer of the epithelium, between epithelial cells and connective tissue cells. The MP of the periodontium are the results of the melanin granules transfer from the melanocytes to the keratinocytes, in a process called epidermal melanin. This study aims to report a clinical case of dermabrasion for treatment of gingival melanin hyper pigmentation of a female patient, 21 years of age, non smoker, under orthodontic treatment and without systemic alterations. This patient attended the Clinic of Specialization in Periodontics of the Brazilian Association of Dentistry (ABO) with the aesthetic of her smile as the chief complain, due to the excess of melanin on the gingival tissues, in the anterior superior region. The epithelial dermabrasion technique, with hand tools, promoted aesthetic results on the melanic depigmentation.